Determination of Folate in Infant Formula and Adult/Pediatric Nutritional Formula by Ultra-High Performance Liquid Chromatography-Tandem Mass Spectrometry: First Action 2013.13. (27th November 2019) - Meisser-Redeuil, Karine; Bénet, Sylvie; Gimenez, Catherine; Campos-Giménez, Esther; Nelson, Maria
Abstract: A UHPLC-MS/MS method for the determination of folate (vitamin B9 ) in infant formula and adult/pediatric nutritional formula was assessed for compliance with standard method performance requirements set forth by the AOAC INTERNATIONAL Stakeholder Panel for Infant Formula and Adult Nutritionals (SPIFAN). A single-laboratory validation (SLV) study was conducted as the first step in the process to validate the method. In the study, 12 matrixes, representing the range of infant and adult nutritional products, were evaluated for folate [the sum of supplemental folic acid plus 5-methyl tetrahydrofolic acid (5-Me THF)]. Method response was linear in the range of 1.0–900 ng/mL, corresponding to 0.33–300 μg/100 g in reconstituted sample. LOD for folic acid and 5-Me THF, expressed in reconstituted product, were 0.10 μg/100 g and 0.05 μg/100 g, respectively, and LOQ were 0.33 μg/100 g and 0.10 μg/100 g, respectively. Repeatability was <5.3% and intermediate precision was <5.5%. Recovery rates of spiking at 50 and 100% of target values in nonfortified products were within 90–110%. Evaluation of trueness was performed on Certified Reference Material (SRM 1849 Infant/Adult Nutritional Formula) and gave 96.4% of theoretical value. Based on the results of the SLV, the method meets the SPIFAN requirements for AOAC First Action status for the determination of folates in infant formula and adult/pediatric nutritional formula.